Tanggapan Pertumbuhan dan Hasil Jagung Manis (Zea Mays Saccharata Sturt.) Terhadap Pemberian Kapur dan Pupuk Kandang Kotoran Ayam - Yulianti Yulianti; Jamzuri Hadie; Chatimatun Nisa (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
One type of popular corn now is sweet corn (Zea mays saccharata Sturt.). The high demand for sweet corn is not balanced by productivity generated. One of the limiting factors in the development of sweet corn on dry land is the low level of soil fertility. The application of lime and chicken manure are the key to improving the fertility of dry land. This research aimed to analyze the effect of the interaction and the single factor of the application of lime and chicken manure to the growth and yield of sweet corn on dry land. Conducted in Hamparaya Village of Batumandi District, Balangan Regency of South Kalimantan Province for three months, starting in August until November 2015. The design of environment that used in this study is a group randomized design (GRD), while the design of treatment is Split Plot Design. There are twelve treatment combinations were repeated three times so that there are 36 experimental plots, on each plot consisted of six plants sample so that the total number of samples was 216 plants. The results showed that the treatment interaction was not significant effect to the growth and yield of sweet corn in Bonanza F1 varieties, but a single treatment of the application of lime in dose 1,5 t ha-1 and chicken manure in dose 5 t ha-1 is the best treatment and able to enhance the growth and yield of sweet corn on dry land.